Effect of Rootstock on the Incidence of Dying Arm of Chenin blanc vines - Ferreira, J. H. S. (South African Journal of Enology and Viticulture, 2017)
A survey was conducted over a period of three seasons to determine the incidence of dying arm on Vi tis vinifera L. cv. Chenin blanc grafted on 11 rootstock cultivars in an existing rootstock trial. A significant seasonal increase in dying arm was observed from 1979 to 1981. Fewer vines with dying arm symptoms occured where Chenin blanc was grafted on V. rupestris cv. Rupestris du Lot and V. champini cv. Ramsey compared to the rest of the rootstock cultivars. Chenin blanc grafted on 101-14 Mgt and 3306 C rootstocks exhibited the highest incidence of dying arm symptoms. This difference in disease incidence in rootstock cultivars is of utmost importance and could be helpful in controlling the disease.